Educating Jurors on Instructions and Legal-ease Objectivity in the California Legal System - Russ K. E. Espinoza; John Coleman; Jennifer V. Coons (Research Developments in Arts and Social Studies Vol. 3, 2022)
Jurors often describe confidence in understanding juror instructions and legal terminology during criminal court trials. However, much research has demonstrated this not to be the case. In California, past legal terminology instructions (Caljic), has been replaced with newer, and purported to be easier understood, instructions (Calcrim). But do these newer instructions improve juror comprehension? The purpose of this research is to empirically examine these two forms of juror instructions. Three hundred and twelve native English speakers acted as mock jurors, reading from a trial transcript with varying Juror instructions (Calcrim, Caljic, or non-descript instructions). Jurors were required to render a verdict, propose a sentence, and be questioned on comprehension, the legal definitions of reasonable doubt, circumstantial and direct evidence, and intent after the trial transcript was completed. The new instructions were substantially better understood by jurors than the old instructions, according to the findings. Jurors given the new instructions were much more likely than those with the previous instructions to achieve a proper verdict. It was also demonstrated that in the novel instruction condition, jurors were considerably better at identifying reasonable doubt and evidence than in the old and non-descript circumstances.